1972
DOI: 10.1002/jsfa.2740230711
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical behaviour of the proteins of the orange

Abstract: Gel filtration of the proteins isolated from orange juice showed three fractions. The two with higher molecular weight were used to prepare rabbit immunosera. By testing the immunosera with concentrated orange and lemon juice substantial differences between the proteins of these two citrus fruits were demonstrated. Our research has also shown that these sera can be used for analysis of commercial products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Proteins might be specific enough to characterize the various parts of citrus fruits and might be species-specific, too. Differences in protein composition of the exo-, meso-, and endocarp of citrus fruits (18) and species-specific immunogenicity of orange and lemon juice were reported (19) earlier. A method based on immunodiffusion has been worked out by Firon et al (20) for the determination of the juice content in commercial products using an antiserum developed against the total protein content of the orange juice.…”
Section: Introductionsupporting
confidence: 58%
“…Proteins might be specific enough to characterize the various parts of citrus fruits and might be species-specific, too. Differences in protein composition of the exo-, meso-, and endocarp of citrus fruits (18) and species-specific immunogenicity of orange and lemon juice were reported (19) earlier. A method based on immunodiffusion has been worked out by Firon et al (20) for the determination of the juice content in commercial products using an antiserum developed against the total protein content of the orange juice.…”
Section: Introductionsupporting
confidence: 58%
“…It is claimed that investigations of bioactive substances and proteins might be specific enough to characterize the various citrus fruits (Clements, 1966). Differences in protein composition of the exo-, meso-, and endocarp of citrus fruits (Clements, 1966) and species-specific immunogenicity of citrus juice have been reported (Cantagalli et al, 1972). Gorinstein et al (2001a) suggested that investigation of antioxidant compounds could reveal possible differences between cultivars of the same citrus fruit.…”
Section: Introductionmentioning
confidence: 99%